Ionic conductivity of MG30-PEMA blend solid polymer electrolyte / Siti Fadzilah Ayub … [et al.] - Ayub, Siti Fadzilah; Nazir, Khuzaimah; Aziz, Ahmad Fairuz; Saaid, Siti Irma Yuana; Yahya, Muhd Zu Azhan; Ali, Ab Malik Marwan (Institute of Research Management and Innovation (IRMI), 2015)
This paper presents on ionic conductivity of MG30-PEMA blend solid polymer electrolytes (SPEs) prepared by solution cast technique. The analysis has shown that conductivity increases with the increasing salt composition. It is observed via x-ray diffraction analysis that the crystallinity of the sample decreased with the amount of salt composition as expected. It is also observed that the dielectric value increases with increasing amount of LiCF₃S0₃ in the sample. Surface morphology revealed that ion aggregation occurred after optimum conductivity which has lowered the conductivity.